RESEARCH ON THE CURRENT SITUATION AND COUNTERMEASURES OF GUANGXI-ASEAN TELECOM NETWORK FRAUD - Hua, Huang Yue (Universitas Nasional, 2020)
Guangxi is connected with many countries of ASEAN, and its geographical advantages have brought a lot of dividends to the bilateral economy. Besides, many negative factors have also quietly emerged. Telecommunication fraud is a new type of crime, which is not only rampant in China, but also a serious disaster area. It has brought many challenges to the rule of law in ASEAN countries. This Journal only takes Guangxi ASEAN telecommunication fraud as the research object, analyzes the current situation and characteristics of transnational telecommunication network fraud, and then analyzes the judicial dilemma of transnational crackdown on telecommunication network fraud and puts forward countermeasures in combination with judicial practice. Keywords: Transnational, Telecommunication Network Fraud, Jurisdiction. Abstrak Guangxi terhubung dengan banyak negara ASEAN, dan keunggulan geografisnya telah membawa banyak keuntungan bagi ekonomi bilateral. Selain itu, banyak faktor negatif juga diam-diam muncul. Penipuan telekomunikasi adalah jenis kejahatan baru, yang tidak hanya merajalela di Tiongkok, tetapi juga daerah bencana yang serius. Ini telah membawa banyak tantangan pada supremasi hukum di negara-negara ASEAN. Jurnal ini hanya mengambil Guangxi ASEAN menegnai telekomunikasi sebagai objek penelitian, menganalisis situasi saat ini dan karakteristik penipuan jaringan telekomunikasi transnasional, dan kemudian menganalisis dilema yudisial penumpasan transnasional pada penipuan jaringan telekomunikasi dan mengajukan langkah-langkah penanggulangan dalam kombinasi dengan praktik peradilan.